The Use of Social Networking Sites in Education: A Systematic Literature Review - Putri, Ratu Mega Maulina; Ghina, Annisa; Suryatini, Ni Wayan; Tripeni, Puput; Irwansyah (Universitas Pendidikan Ganesha, 2023)
Social Networking Sites (SNS) have emerged as a consequential implication of technological advancements that play an important role in human life today. The presence of Social Networking Sites (SNS) as a rapidly evolving technology constitutes a global phenomenon that warrants comprehensive examination from various perspectives, with education standing out as one of the most pertinent areas of inquiry. It is necessary to understand the usage of SNS in education in order to better empower them within learning activities. The purpose of this study is to analyze extent SNS is used in the field of education, aiming to empower SNS even further in future learning activities. This systematic literature review refers to 60 Scopus-indexed journal articles that have been adjusted to the concept under further review, namely SNS and education, along with substantively relevant keywords. This research presents eight research questions regarding the conceptual framework, characteristics of journal articles, research findings, and research development. The analysis results indicate that the use of SNS in education plays a significant role for academics and students, and it can support the educational institutions’social life and aspects of teaching, learning, and research.